Analisis Manajemen Kurikulum Pembelajaran di Pondok Pesantren Tahfidz Qur’an - Miftahur Rohman; Rina Mida Hayati (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
Tahfidz curriculum management is one of the important things in education management, because without a good and appropriate curriculum, it will be difficult to achieve the goals and objectives of education that have been aspired by an educational institution. The purpose of the research was to know deeper about the implementation of curriculum management at Islamic Boarding School Bustanul Ulum Jayasakti Lampung Tengah. This research method uses descriptive qualitative with a case study. Data collection techniques used were interviews, observation and documentation. The data obtained was then analyzed using the stages of data condensation, data presentation, and drawing conclusions. The findings shows that, curriculum planning which begins with strategic planning, program planning, and learning activity planning; implementing of curriculum; curriculum implementation in learning activities includes the diniyah program and tahfidz program which are classified into three levels of basic classes, tahsin, and tahfidz; and evaluation of the curriculum with daily, weekly and monthly evaluations, with the aim of achieving better results in memorizing the Qur'an